Theoretical aspects of studying of the innovations commercialization process - Mamrayeva, D.G.; Toxambayeva, A.B.; Mamrayeva, G.B.; Rodina, L.A. (BUKETOV BUSINESS REVIEW, 2020)
Object: to consider theoretically-methodological aspects, also management mechanisms by the process of innovations commercialization. Methods: methods of system and structural analysis are used in the article, allowing to consider the scientific problems investigated in the article in a comprehensive manner, also draw conclusions that fully reveal the essence and specifics of the studied research object. Findings: modern trends in the theory of innovations commercialization considered in the article, studied the conceptual apparatus in the field of innovations commercialization; the process of innovations commercialization is investigated, the relationship of its participants is established, the ways of its implementation are determined; the stages and phases of the innovation process are concretized. Conclusions: the concept of innovations commercialization, the innovation process, the stages of its implementation is investigated in presented scientific article. The article describes the main phases and stages of the innovation process, analyzes the model of commercialization of innovations, also the criteria of the degree of its successful implementation. The ways of innovations commercialization, which are the most relevant today are characterized, the potential profit for a certain period, the main items of the enterprise income and expenses with successful implementation of the process of innovations commercialization are presented. The formulas of the potential profit calculating for a certain period of innovative product commercialization are reflected. In the analyzed scientific studies of foreign and domestic researchers, by the authors concluded that in the conditions of modern economic development, the restructuring of a number of the world countries economies the into digital and innovative components, commercialization is one of the most important components of the successful implementation of the innovation results, therefore, it is advisable to carry out this process at an earlier stage, starting from the moment of fundamental research by companies in the structure of their activities in the field of R&D.